World Rabies Day 2020: Kolaborasi Berkualitas dan Vaksinasi Tuntas untuk Kalimantan Barat Bebas Rabies - Khariri Khariri; Sri Wahyuni (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Rabies is a zoonotic disease that has been known for a long time. This infection attacks the central nervous system with the main sign of progressive paralysis and ending in death. Transmission can occur when humans are bitten by animals infected with rabies. Some animals can transmit rabies, especially dogs and cats. In commemoration of World Rabies Day, the Food, Animal Husbandry and Animal Health Office of West Kalimantan Province provides free services in the form of rabies vaccination and dog and cat sterilization. This activity is not only aimed at providing rabies vaccination services for dogs and cats in the vicinity of Pontianak and Kubu Raya, but also at the same time educating pet owners about rabies. Data collection was carried out by observing and documenting activities. Data analysis was carried out in descriptions that describe the process of activities. This activity was carried out in the Hall of the Food, Animal Husbandry and Animal Health Service of West Kalimantan Province on September 26, 2020. Of the target 100 doses can only be given as many as 71 doses consisting of 54 doses for cats and 17 doses for dogs, while sterilization was successfully carried out on 15 individuals. Cats and 15 dogs. Vaccination, which is usually given to rabies-infected animals, is a very effective preventive measure. Through the sterilization program, it is hoped that it can reduce the overpopulation of dogs and dogs.